As políticas educacionais implementadas pela Secretaria Municipal de Educação de Itaituba/PA de 1997-2016 - SANTOS, Gisele da Silva Lopes dos (Universidade Federal do Oeste do Pará, 2021)
The present research discusses educational policies at the municipal level, whose main objective is to identify the educational policies implemented by the Itaituba / PA Municipal Department, from 1997 to 2016, considering the historical and legal frameworks of Brazilian education, such as the Law of Guidelines and Bases of National Education - LDB nº 9.394 / 96, Federal Constitution of 1988, highlighting the process of municipalization of education and educational reforms occurred since 1990, which allowed the historical record of policies aimed at improving education municipal. Among the theoretical foundations are the contributions of Sousa (2006), Libâneo (2016), Frigotto and Ciavata (2003), Oliveira (2009) and Sanfelice (2016), who address education as a public social policy and school education as everyone's right and duty of the State. As for the methodological assumptions, we used qualitative research, based on the case study of the Municipal Secretariat of Education as a locus of analysis and as categories of analysis: democratic management, teacher training, physical and didactic-pedagogical-curricular network. As a tool for data collection, we used document analysis (primary and secondary sources) and semi-structured interviews. The results pointed out, considering the process of decentralization of autonomy, foreseen by LDB 9394/96 and CF 1988, that the municipality underwent a period of adaptation and administrative learning, facing the challenges of municipalization of education. Semed has undergone restructurings both in physical infrastructure and in increasing the number of servers to meet the new demands of education. As for the educational service, at the beginning of the process of municipalization of education, in 1998, there was an increase in the number of students, requiring the management, reforms, extensions and construction of new schools, as well as hiring of personnel and public tendering. Fundef Fundamental Education Development Fund was fundamental for these investments. The results also point to the stagnation of state public education, disproportionate to the growth of municipal public education, in quantitative terms (number of schools, teachers and enrollments), which suggests a lack of collaboration between the state and the municipality. Despite the attempt of collective participation in the elaboration of educational policies, the municipal and state networks seem to move parallel. Governments have taken important steps towards democratic management, encouraging community participation in municipal education decisions. The teacher training, from the first management was prioritized by Semed projects. The expansion of the physical network and school reforms were a priority at the beginning of municipalization, since the municipality needed to adapt to the new reality. In the last three administrations, it is important to highlight the importance of the National Education Development Fund (FNDE) for reforms and expansion of the physical network of schools. The didactic-pedagogical-curricular programs and projects of the last administrations presented a close relationship with the system of evaluation of basic education - SAEB, aimed at increasing the Basic Education Development Index - Ideb. In summary, despite advances in municipal education, as well as the reality of other Brazilian municipalities, especially those in the state of Pará, there is still much that needs to be improved in the infrastructure of schools and the valuation of education professionals for the provision of a quality education.